2005
DOI: 10.1111/j.1440-1797.2005.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of peroxisome proliferator activated receptor gamma agonists on diabetic and non‐diabetic renal diseases

Abstract: Peroxisome proliferator activated receptor gamma (PPARgamma) agonist has not only antidiabetic effect but also a protective effect against various types of injury of the kidney. The protective effects of PPARgamma agonists are observed in diabetic nephropathy and non-diabetic renal diseases such as 5/6 ablation model of renal failure, experimental glomerulonephritis, ischemia-reperfusion injury, hypertensive nephropathy and cyclosporin-induced renal injury. The mechanism of renoprotection by PPARgamma agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…In addition to their vasodilating effects on the glomerular efferent arterioles [31], their above described effects regarding lowering blood pressure as well as protecting endothelial function may possibly be involved. Additionally, reno-protective effects of PPARγ ligands in non-diabetic renal diseases have recently been reported [34], indicating the general usefulness of PPARγ ligands on chronic kidney disease. We have also demonstrated reno-protective effects of TZD rosiglitazone against cyclosporine-induced renal injury in Sprague-Dawley rats [35].…”
Section: Effects Of Pparγ On Atherosclerosismentioning
confidence: 99%
“…In addition to their vasodilating effects on the glomerular efferent arterioles [31], their above described effects regarding lowering blood pressure as well as protecting endothelial function may possibly be involved. Additionally, reno-protective effects of PPARγ ligands in non-diabetic renal diseases have recently been reported [34], indicating the general usefulness of PPARγ ligands on chronic kidney disease. We have also demonstrated reno-protective effects of TZD rosiglitazone against cyclosporine-induced renal injury in Sprague-Dawley rats [35].…”
Section: Effects Of Pparγ On Atherosclerosismentioning
confidence: 99%
“…16,17). This protection reflects both improved glucose metabolism and insulin resistance as well as the antiinflammatory, antifibrotic, and antiapoptotic effects of PPARγ ligands (18).…”
Section: Role Of Ppars In Different Organs After I/r Injurymentioning
confidence: 99%
“…PPAR-γ had some anti-inflammatory effects on inflammatory bowel disease and rheumatoid arthritis [30,31] . It ameliorates the inflammatory cell infiltration and downregulates the proinflammatory cytokine expression in animal models of diabetic nephropathy and lupus nephropathy as well as in mesangial cells, fibroblasts and tubular epithelial cells [32,33] . Li and colleagues demonstrated that eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) could downregulate LPS-induced MCP-1 expression via the PPAR-γ pathway [34] .…”
Section: Discussionmentioning
confidence: 99%